Effects of education on self-monitoring of blood pressure based on BASNEF model in hypertensive patients - Mohammad Hossein Baghianimoghadam (Journal of Research in Medical Sciences, 2010)
Abstract
Introduction: The high prevalence of hypertension along with its serious complications on the body, have made this disorder to an important health problem. Hypertension monitoring in the house may be an effective method. Therefore, the aim of this study is to explore the effectiveness of education on blood pressure self-monitoring in patients with hypertension based on BASNEF model.
Materials and Methods: In this clinical trial, 150 outpatients with hypertension referring to a private clinic in Yazd, Iran were recruited in the study. The data were collected by a validated and reliable questionnaire. The implementing educational program was continued for 2 months. BASNEF model applied to distinguish the behavior.
Results: The respondents acquired 17.72% of total hypertension self-monitoring behavior score, 47.03% of attitude, 12.37% of subjective norms, 33.46% of intention and 50.95% of enabling factors. After intervention there were significant increases in self-monitoring behavior (173.31%), attitude (62.60%), subjective norms (54.70%), intention (129.93%) and enabling factors (46.62%) in intervention group.
Conclusion: The results of this study showed that the level of self-monitoring behavior in the patients was low. Educational programs, like what we implied in our study, in order to improve self-monitoring behavior in patients with hypertension may be helpful and necessary.